2017
DOI: 10.1093/ijnp/pyx015
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Inflammation in Early Onset First Episode Psychosis: A Systematic Review and Meta-Analysis

Abstract: Background:People with schizophrenia and other psychosis show increased proinflammatory and prooxidative status. However, the few studies that have specifically assessed oxidative and inflammatory markers in early onset psychosis (onset before age 18) have shown contradictory results.Methods:Preferred Reporting Items for Systematic Reviews and Meta-analyses guidelines for systematic reviews and meta-analyses were used to conduct a systematic literature search to detect studies comparing inflammatory and oxidat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
72
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 61 publications
3
72
0
Order By: Relevance
“…(2013) found an increase in blood markers of lipid peroxidation (i.e., MDA and/or TBARS) in SZ, already present in first‐episode psychotic patients . However, in individual studies, 8‐OHdG was found to be increased in patients with non‐remitting schizophrenia although not in adolescents with a first psychotic episode, suggesting its association with a chronic disease course . In depression, Jiménez‐Fernández et al.…”
Section: Discussionmentioning
confidence: 99%
“…(2013) found an increase in blood markers of lipid peroxidation (i.e., MDA and/or TBARS) in SZ, already present in first‐episode psychotic patients . However, in individual studies, 8‐OHdG was found to be increased in patients with non‐remitting schizophrenia although not in adolescents with a first psychotic episode, suggesting its association with a chronic disease course . In depression, Jiménez‐Fernández et al.…”
Section: Discussionmentioning
confidence: 99%
“…The complex nature of psychiatric illness, as well as the difficulty in GSH measurement, leaves a heterogeneous evidence base that makes comparison challenging. Contradictions between studies assessing brain GSH make it difficult to compare brain and blood GSH, where studies assessing blood GSH present consistent findings in perturbation in GSH metabolism for first‐episode psychosis (Fraguas, Díaz‐Caneja, Rodríguez‐Quiroga, & Arango, ), schizophrenia (Ng, Berk, Dean, & Bush, ), bipolar disorder and autism (Gu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…There is a considerable lack of diagnostic and/or predictive markers in psychiatry that are valid and easy to use for the transfer into a clinical setting (Venkatasubramanian and Keshavan, 2016). However, within recent years an increasing amount of evidence has been accumulated that inflammatory (Fraguas et al, 2017), genetic (Breitenstein et al, 2015) or neuroimaging biomarkers (e.g. Xia et al, 2018) have discriminative or predictive power, although the associations between markers and treatment response are sometimes counter-intuitive.…”
Section: Discussionmentioning
confidence: 99%